IMPLEMENTASI PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL DALAM PRESENTASI FINANCIAL SOFT SKILL DI SMP NASIONAL BANDUNG - Wahyu Trimasuti; Sali Setiatin; Santy Christinawati; Rita Zulbetti (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the implementation of the use of audio-visual-based learning media in the presentation of financial soft skills at the Bandung National Junior High School. The number of participants who took part in the financial soft skills activities at the Bandung National Junior High School were 31 students. This type of research is descriptive qualitative research. The research data were collected by several techniques, namely observation, interviews and documentation. The triangulation technique is carried out by the triangulation method, namely by re-checking the information from interviews with documentation and observation. This study found that the use of audio-visual-based learning media in the presentation of financial soft skills at the Bandung National Junior High School has many advantages; 1) Students do not get bored quickly and enthusiastically in learning; 2) To improve students' understanding; 3) To increase students' learning motivation, and 4) Learning can be achieved well. Suggestions that can be used as input, one of which is for teachers. Researchers suggest teachers to always improve their creativity in finding ways that can be used to adjust students in the classroom.